DFT calculations of the main optical constants of the Cu2ZnSnSexS4-x system as high-efficiency potential candidates for solar cells - Dilshod Nematov (International Journal of Applied Power Engineering (IJAPE), 2022)
In the present work, using quantum-chemical calculations in the framework of density functional theory (DFT), we study the optical properties of semiconductor nanocrystals of kesterite Cu2ZnSnS4 doped with Se. Using the WIEN2k package, the concentration dependences of the optical characteristics of nanocrystals of the Cu2ZnSnSexS4-x system (x = 0, 1, 2, 3, 4) were calculated. It is shown that doping with Se at the S position leads to a noticeable improvement in the photo absorbing properties of these nanocrystals, as well as their photoconductivity in the IR range. The calculated absorption and extinction spectra of the materials under study, are compared with experimental data known from the literature. The data obtained will significantly enrich the existing knowledge about the materials under study and will help expand the scope of these compounds in optoelectronic devices, especially in solar cells and other devices that convert solar energy into electricity.